2011
DOI: 10.1108/14779961111167649
|View full text |Cite
|
Sign up to set email alerts
|

Toward a normative ethics for technology development

Abstract: Purpose -The purpose of this paper is to criticise ad hoc approaches to ethics in research and development in technology as descriptive and non-ethical, and based upon a narrow conception of rationality. Design/methodology/approach -The approach deploys a theory of normativity that can incorporate values and a broad conception of rationality, in order to account for the relevance of issues for the addressees of normative injunctions. Findings -A normative approach is possible and required in order to implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…It is important to note that in this era, where virtual acts are essentially more common than direct ones, relies on knowledge which is frequently adapted to the changing environment when it is produced. The attainment of mixing and matching rates of knowledge as a development for a dynamic within an everlasting world can be seen as a byproduct of the control that humans have attained in understanding the knowledge about how we relate to the world embedded within the human genome, generated in association with technology and freely available on the internet, and so it raises questions about our assumptions of control (Prior et al, 2002;Rainey and Goujon, 2011). Driving evolutionary systems which enable to make knowledge increasingly become more mobilised to manage, software agents with replacing the search function of unknowingly matching words will exchange knowledge without human intervention.…”
Section: Ethical Perspectives In Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that in this era, where virtual acts are essentially more common than direct ones, relies on knowledge which is frequently adapted to the changing environment when it is produced. The attainment of mixing and matching rates of knowledge as a development for a dynamic within an everlasting world can be seen as a byproduct of the control that humans have attained in understanding the knowledge about how we relate to the world embedded within the human genome, generated in association with technology and freely available on the internet, and so it raises questions about our assumptions of control (Prior et al, 2002;Rainey and Goujon, 2011). Driving evolutionary systems which enable to make knowledge increasingly become more mobilised to manage, software agents with replacing the search function of unknowingly matching words will exchange knowledge without human intervention.…”
Section: Ethical Perspectives In Technologymentioning
confidence: 99%
“…Furthermore, innovations in shaping the human experience increasingly act to engage people with media entertainment and information to connect those interested with each other (Rainey and Goujon, 2011). This would potentially result in humans being increasingly engaged with media platforms, services and content.…”
Section: Ethical Perspectives In Technologymentioning
confidence: 99%
“…Several previous studies have found partial relationship between variables as follow: the effect of task characteristics toward the TTF by Huscroft et al (2013); Wu et al (2018); Isaac et al (2017) and Ferreira et al (2017); the effect of technology characteristics toward the TTF by Rainey and Goujon (2011); Razmak and Bélanger (2018); Huscroft et al (2013) and Babu and Heath (2017); the effect of the TTF toward the use by Barhoumi (2016); Glowalla and Sunyaev (2014); Román and Rodríguez (2015) and Norzaidi and Zakaria (2017); and the effect of the use toward the TTF by Barhoumi (2016); Wu et al (2018) and Raj and Troutt (2009). …”
Section: Introductionmentioning
confidence: 95%
“…the effect of technology characteristics toward the TTF by Rainey and Goujon (2011); Razmak and Bélanger (2018); Huscroft et al (2013) and Babu and Heath (2017);…”
Section: Introductionmentioning
confidence: 99%
“…La importancia del estudio de la ética en las distintas profesiones radica en que, sin una idea de las normas éticas vinculadas al contexto de cada actividad, sería incomprensible que cualquier decisión tomada pueda ser moralmente convincente (Rainey & Goujon, 2011), sobretodo, entre las alternativas que se encuentran en determinadas situaciones problemáticas (Frey, 2010). Por lo tanto, se debe desafiar a los estudiantes a descubrir cómo estas opciones (toma de decisiones) forman la ética y los valores profesionales (Walther, 2016).…”
unclassified